Wandering as a Sociomaterial Practice: Extending the Theorization of GPS Tracking in Cognitive Impairment. (February 2019) - Wherton, Joseph; Greenhalgh, Trisha; Procter, Rob; Shaw, Sara; Shaw, James
Electronic tracking through global positioning systems (GPSs) is used to monitor people with cognitive impairment who "wander" outside the home. This ethnographic study explored how GPS-monitored wandering was experienced by individuals, lay carers, and professional staff. Seven in-depth case studies revealed that wandering was often an enjoyable and worthwhile activity and helped deal with uncertainty and threats to identity. In what were typically very complex care contexts, GPS devices were useful to the extent that they aligned with a wider sociomaterial care network that included lay carers, call centers, and health and social care professionals. In this context, "safe" wandering was a collaborative accomplishment that depended on the technology's materiality, affordances, and aesthetic properties; a distributed knowledge of the individual and the places they wandered through, and a collective and dynamic interpretation of risk. Implications for design and delivery of GPS devices and services for cognitive impairment are discussed.